Differences in Age Estimated by the Kvaal Method on Right and Left Mandibular Canines - Kusumaningrum, Sulistyani; Wasita, Brian; Wujoso, Hari; Rahayu, Rachmi Fauziah; Hermansyah, Muhamad Lukman; Lawei, Tharina (Indonesian Journal of Medicine, 2021)
Background: The radiographic method for determining the estimated age has the advantage of being non-invasive and the orthopantomogram images are digitally processed. Canines have a strong correlation with chronological age and have good resistance and large pulp space. This study aimed to determine the difference in age estimates using the Kvaal method on the right and left mandibular canines.Subjects and Method: There were 80 orthopantomogram samples from dental and oral clinic patients who had undergone orthopantomography at the Radiology Installation of Dr. Moewardi Hospital, from January 2019 to December 2020. The estimated age of right and left canines was calculated based on the Kvaal method and performed a T-test.Results: At the estimated age of the right and left mandibular canines determined by the Kvaal formula, the T-test was performed showing a mean of 38.3 years for the right mandibular canine (Mean= 38.3; SD= 6.7) and 38.2 year the left mandibular canine (Mean= 38.2; SD= 8.9), with p = 0.910. Data analysis showed that there was no difference in age estimation using the Kvaal method on the right and left mandibular canines.Conclusion: There was no difference in age estimates by the Kvaal method on the right and left mandibular canines.Keywords: Oratopantomogram, Metoday Qual, Kaninus MandibulaCorrespondence: Sulistyani Kusumaningrum. Department of Radiology Dr. Moewardi Hospital / Faculty of Medicine Universitas Sebelas Maret, Surakarta. Email: kusumasulis1@gmail.com.Indonesian Journal of Medicine (2021), 06(02): 206-211https://doi.org/10.26911/theijmed.2021.06.02.09